Existence theorem for integral inclusions by a fixed point theorem for multivalued implicit-type contractive mappings - Ali, Muhammad Usman; Pitea, Ariana (Nonlinear Analysis: Modelling and Control, 2021)
In this article, we introduce fixed point theorems for multivalued mappings satisfying implicit-type contractive conditions based on a special form of simulation functions. We also provide an application of our result in integral inclusions. Our outcomes generalize/extend many existing fixed point results.